Szociális munka idősekkel: Felmérés és intervenció – egy biopszichoszociális megközelítés - Szabó, Lajos (Párbeszéd: Szociális munka folyóirat, 2014)
Kathleen McInnis-Dittrich: Social Work with Older Adults:A Biopsychosocial Approach to Assesment and Intevention – Third Edition(Allyn and Bacon, Boston, 2009 – Pearson Education Inc.)